Microscopic wettability of carbonate rocks: a proton field cycling NMR approach - Freiman, Gabriel; Korb, Jean-Pierre; Nicot, Benjamin; Ligneul, Patrice (Diffusion Fundamentals, 2009)
Nuclear Magnetic Relaxation Dispersion (NMRD) is strongly sensitive to the microscopic wettability of oil and brine bearing carbonate rocks. Exploring a very large range of low frequency enables isolating the typical NMRD dispersion features, 1/T1Surf, associated to the different processes of molecular surface dynamics. This allows a separation of the surface and bulk microdynamics of oil and water even for a biphasic saturation of petroleum rocks. Several surface dynamical parameters were determined and related to the concept of microscopic wettability of oil and water in porous media.